Mass spectrometric analysis for nuclear safeguards. Issue 7 (24th July 2015) - Boulyga, Sergei; Konegger-Kappel, Stefanie; Richter, Stephan; Sangély, Laure
<x xml:space="preserve">Abstract</x> An important part of the International Atomic Energy Agency (IAEA) safeguards system is the "analytical laboratory", with mass spectrometric techniques, belonging to the most powerful methods for the analysis of nuclear material and environmental samples collected during inspections.